Coking of high-viscosity water-containing oil - A. I. Nikolaev; B. V. Peshnev; E. V. Egorova (Тонкие химические технологии, 2022)
Objectives. A characteristic feature of oil production is an increase in the volume of highviscosity bituminous oil. In Russia, technologies based on the use of water vapor are used for their extraction. The use of such technologies leads to a large amount of water in the product stream from the production well. Preparation of oil for processing involves its stabilization, desalination, and dewatering. Since the densities of the extracted oil and the water contained in it are comparable, traditional preparation schemes for processing of high-viscosity bituminous oil are ineffective. One of the possible solutions to the problem involving such oil in the fuel, energy, and petrochemical balance is to use a coking process at the first stage of its processing. This aim can be achieved by studying the influence of the process conditions of coking high-viscosity water-containing oil on the yield and characteristics of the resulting products.Methods. Coking of oil with a density of 1.0200 g/cm3 at 50 °C and with 18 wt % water content was carried out in a laboratory installation in a “cube.” A hollow cylindrical apparatus was used as a reactor and was placed in a furnace. The temperature and pressure in the reactor were maintained at 500–700 °C and 0.10–0.35 MPa, respectively.Results. An increase in the coking process temperature results in an increase in the amount of gaseous products, a decrease in the amount of the coke generated, and a higher dependence of the amount of liquid products on temperature with a maximum yield at 550–600 °C. The process temperature also affects the composition of liquid products. At a lower temperature, the amount of gasoline and kerosene fractions in liquid products is higher. With an increase in pressure, a higher amount of gaseous products, coke, and low-molecular-weight hydrocarbon fractions in liquid products could also be obtained. The characteristics of the coke produced in the coking process are similar to those of commercially produced grades. It is noted that when coking water-containing oil, up to 98% of the emulsion water goes with liquid products, and the remaining amount of water remains in the formed coke.Conclusions. Results showed the possible application of the coking process at the initial stage of processing high-viscosity bituminous oil. In this case, the dewatering stage is significantly simplified since the technological scheme of delayed coking allows the separation of the gasoline fraction from water.